Lithium-mixed coated modified ternary positive electrode material as well as preparation method and application thereof
By using a variety of lithium compound mixing and doping technologies in the ternary positive electrode material, the double-layer fast ion conductor cladding layer is solved, and the existing materials are insufficient performance under high voltage and high nickel conditions is achieved, and cost reduction is achieved and performance improvement, suitable for secondary battery applications.
Patent Information
- Application Number
- CN202411260028.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing ternary cathode materials have insufficient safety, cycle performance and cost under high voltage and high nickel conditions, and the high cost of lithium resources affects battery production, requiring a solution that can reduce costs and improve performance.
A variety of lithium compounds are mixed in a certain proportion, and a double-layer fast ion conductor coating is formed through doping and surface gradient coating to improve the safety performance, cycling performance and power performance of the material. The specific method includes using Li(NixCoyMn1-x-y)z(YaWbAlcZrdBe)f PO4 as the core, Li3Alx1Tiy1(PO4)3 as the first cladding layer, and LiTix2(PO4)3 as the second cladding layer, through multiple sintering and doping The combination of miscellaneous agents forms a composite modified material.
It significantly improves the discharge specific capacity, first-time efficiency, safety performance and cycling performance of the positive electrode material under high voltage or high power conditions, reduces the solubility of manganese in organic electrolyte, broadens the distance between ion channels and layers, and improves the The high-temperature electrochemical properties of the material reduce the degree of Li/Ni mixed displacement and ensure the application performance of battery products.
Smart Images

Figure CN119133403A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery raw materials, and in particular to a mixed lithium-coated modified ternary positive electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy vehicles, the demand for power batteries continues to increase. However, the core factors that affect or restrict the development of power batteries are resources such as nickel, cobalt, and lithium. Among them, lithium resources have a crucial impact on the cost of batteries and vehicles. At the same time, ternary positive electrode materials have obvious shortcomings compared with lithium iron phosphate positive electrode materials, and it is extremely important to improve and enhance their safety and cycle performance. The lithium source raw materials used in the preparation of traditional positive electrode materials are mainly lithium carbonate and lithium hydroxide monohydrate. Affected by current international and domestic resources and prices, the use of lithium compound products with certain cost advantages or composite lithium source application process solutions can continuously reduce costs and enrich available resources and solutions. Compared with battery-grade lithium carbonate or lithium hydroxide, the price of lithium phosphate is only 60% of the former, and in the precipitation of lithium phosphate Li + In the process, Li + The utilization rate is high, and the Li content in the remaining lithium precipitation mother liquor is less than 5%. Therefore, it is quite advantageous to use lithium phosphate to supplement the current lithium carbonate / lithium hydroxide application. However, the Li3PO4 currently prepared by recycling lithium ore, brine or waste batteries is crude lithium phosphate, which contains a large amount of calcium and magnesium impurities, which affects the performance of the positive electrode material and cannot meet the production of power batteries, so impurities must be removed. After a series of process method improvements and composite process research, the performance of ternary positive electrode materials can be improved.
[0003] The development trend of ternary positive electrode materials for new energy lithium batteries is high voltage, single crystal, and high nickel. At the same time, battery safety, charging time, and battery life have always troubled many enterprises, scientific research institutions, and users. The use of mixed lithium and doping and surface gradient coating to jointly construct a fast ion conductor coating layer is beneficial to improving the safety performance, cycle performance, rate performance, gram-to-weight capacity, and first efficiency of the positive electrode materials. Summary of the invention
[0004] One of the purposes of the present invention is to provide a mixed lithium-coated modified ternary positive electrode material, which adopts a variety of lithium compounds as lithium sources in a certain proportion for mixing and co-doping with other metal compounds, and then uses different types of lithium-containing compounds and other metal compounds for surface gradient coating to form a surface double-layer fast ion conductor coating layer. The finished ternary positive electrode material has good physical and chemical properties and application properties. The positive electrode material has significantly improved discharge specific capacity, initial efficiency, safety performance, cycle performance and power performance under high voltage or high power conditions.
[0005] The second object of the present invention is to provide a method for preparing the above-mentioned mixed lithium-coated modified ternary positive electrode material.
[0006] The third object of the present invention is to provide an application of the above-mentioned mixed lithium-coated modified ternary positive electrode material in the preparation of secondary battery positive electrode sheets or secondary batteries.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] In the first aspect, the present invention provides a lithium-coated modified ternary cathode material, such as Figure 1 As shown, it includes a core, and a first coating layer and a second coating layer on the surface of the core;
[0009] The general formula of the core is Li(Ni x Co y Mn 1-x-y ) z (Y a W b Al c Zr d B e ) f PO4, where 0.5≤x<1.0, 0<y≤0.40, 0.97≤z<1.0, 0<a≤0.0025, 0<b≤0.009, 0<c≤0.008, 0<d≤0.0085, 0<e≤0.002, a+b+c+d+e=f, z:f=(0.97-1.0):(0.0004-0.03), z+f=1;
[0010] The general formula of the first coating layer is Li3Al x1 Ti y1 (PO4)3, where x1 = 0.2-0.8, y1 = 1.2-1.8;
[0011] The general formula of the second coating layer is LiTi x2 (PO4)3, where x2 = 0.8-3.0.
[0012] In a second aspect, the present invention provides a method for preparing the above-mentioned mixed lithium coated modified ternary positive electrode material, such as Figure 2 As shown, the following steps are included:
[0013] (1) Ni x Co y Mn 1-x-y (OH)2 (0.5≤x<1.0, 0<y≤0.40), the first lithium source, the second lithium source and the dopant containing Y / W / Al / Zr / B elements are mixed and sintered for the first time, and then crushed, sieved and demagnetized to obtain the positive electrode material core Li (Ni x Co y Mn 1-x-y )z (Y a W b Al c Zr d B e ) f PO4;
[0014] (2) mixing the positive electrode material core with the first coating agent containing Ti / Al / P / Li elements and performing a second sintering, and then crushing, screening, and demagnetizing to obtain the positive electrode material after the first coating;
[0015] (3) The positive electrode material after the first coating is mixed with the second coating agent containing Ti / P / Li and then sintered for the third time, and then crushed, screened, demagnetized, and batch mixed to obtain a finished positive electrode material after the second coating.
[0016] The following is a detailed description:
[0017] Step (1):
[0018] Selection of ternary cathode material precursor, its small particle size D 50 The particle size of the large particle ternary precursor D 50 It can be 7-16 μm, preferably 9-12 μm.
[0019] The first lithium source is one or more selected from LiOH, LiOH·H2O, Li2CO3, LiNO3 or C2H3O2Li, preferably LiOH or Li2CO3; the second lithium source is Li3PO4. When used, the coarse lithium source particles can be mechanically ground to 2-10 μm or a lithium source of the same specification on the market can be selected, preferably 3-5 μm.
[0020] In some embodiments, the mass ratio of the first lithium source to the second lithium source is 0.5-1.0:0.003-0.5.
[0021] In some embodiments, the ternary cathode material precursor Ni x Co y Mn 1-x-y The ratio of the total molar amount of Ni, Co, and Mn in (OH)2, the molar amount of Li in the total lithium source, and the total molar amount of Y, W, Al, Zr, and B in the dopant is 1: (0.94-1.18): (0.0004-0.0300), preferably 1: (0.96-1.15): (0.0008-0.025), and more preferably 1: (0.98-1.10): (0.001-0.020).
[0022] In some embodiments, the dopant containing Y / W / Al / Zr / B elements is γ-Al2O3, Zr 0.8 O2Y 0.2 , a mixture of WO3 and H3BO3;
[0023] Preferably, the ternary cathode material precursor Ni x Co y Mn 1-x-y The mass ratio of (OH)2 to γ-Al2O3 is 100:(0.03-0.9), preferably 100:(0.08-0.8), more preferably 100:(0.1-0.6);
[0024] Preferably, the ternary cathode material precursor Ni x Co y Mn 1-x-y (OH)2 and Zr 0.8 O2Y 0.2 The mass ratio is 100:(0.04-0.60), preferably 100:(0.06-0.52), more preferably 100:(0.1-0.42);
[0025] Preferably, the ternary cathode material precursor Ni x Co y Mn 1-x-y The mass ratio of (OH)2 to WO3 is 100:(0.02-0.60), preferably 100:(0.05-0.50), more preferably 100:(0.1-0.40);
[0026] Preferably, the ternary cathode material precursor Ni x Co y Mn 1-x-y The mass ratio of (OH)2 to H3BO3 is 100:(0.02-0.7), preferably 100:(0.04-0.6), more preferably 100:(0.08-0.5);
[0027] Preferably, the purity of γ-Al2O3 is ≥99.9%, and its D 50 Particle size 0.04 μm-6 μm, preferably 0.1 μm-5 μm, more preferably 0.4 μm-3 μm;
[0028] Preferably, Zr 0.8 O2Y 0.2 Purity ≥ 99.9%, its D 50 Particle size 0.05 μm-5.0 μm, preferably 0.08 μm-4.0 μm, more preferably 0.5 μm-3.5 μm;
[0029] Preferably, the purity of WO3 is ≥99.9%, and its D 50Particle size 0.04 μm-6.0 μm, preferably 0.06 μm-5.0 μm, more preferably 0.5 μm-3 μm;
[0030] Preferably, the purity of H3BO3 is ≥99.5%, and its D 50 The particle size is 0.2 μm-5 μm, preferably 0.5 μm-4 μm, more preferably 0.8 μm-2.5 μm.
[0031] In some embodiments, the mixing step uses a ball mill or a jar mill, a plowshare mixer or a high-speed mixer to mix the materials evenly, and then put them into a small dry pot or a sagger, shake them evenly and cut them into pieces before the first sintering.
[0032] In some embodiments, the first sintering step includes: heating to 650-1100° C. (preferably 720-1100° C.) and keeping the temperature for 8-24 hours (preferably 9-18 hours) in an oxygen-containing atmosphere (preferably the atmosphere is oxygen with a concentration of ≥95%);
[0033] Preferably, when the first sintering step is carried out in a muffle furnace or a tube furnace mode, the heating rate is controlled to be 1-5°C / min, preferably 2-4°C / min, and more preferably 3°C / min;
[0034] Preferably, when the first sintering step is carried out in an atmosphere roller kiln or a rotary kiln mode, the heating rate is controlled to be 1-30°C / h, preferably 5-20°C / h, and more preferably 10°C / h.
[0035] After the first sintering, the ternary positive electrode material-doped matrix (core) is obtained through coarse crushing, fine crushing, screening and demagnetization for subsequent coating.
[0036] Preferably, the large particle size D50 of the ternary positive electrode material after crushing and sieving is 7-16 μm, preferably 9-12 μm, and the small particle size D50 is 2-6 μm, preferably 2.2-4.6 μm.
[0037] Step (2):
[0038] In some embodiments, the ratio of the total molar amount of Ni, Co, and Mn in the core of the positive electrode material to the total molar amount of Ti, Al, P, and Li in the first coating agent is 1: (0.0001-0.0060).
[0039] In some embodiments, the first coating agent containing Ti / Al / P / Li elements is a mixture of Li3PO4, TiO2 and γ-Al2O3;
[0040] Preferably, the mass ratio of the positive electrode material core to Li3PO4 is 100:(0.02-0.70), preferably 100:(0.05-0.60), more preferably 100:(0.1-0.50);
[0041] Preferably, the mass ratio of the positive electrode material core to TiO2 is 100:(0.01-0.30), preferably 100:(0.04-0.24), more preferably 100:(0.06-0.20);
[0042] Preferably, the mass ratio of the positive electrode material core to γ-Al2O3 is 100:(0.06-0.50), preferably 100:(0.08-0.44), and more preferably 100:(0.1-0.36).
[0043] Preferably, the purity of Li3PO4 is ≥99.5%, and its D 50 Particle size 60nm-120nm;
[0044] Preferably, the purity of TiO2 is ≥99.9%, and its D 50 Particle size 20nm-60nm;
[0045] Preferably, the purity of γ-Al2O3 is ≥99.9%, and its D 50 Particle size 30nm-120nm.
[0046] In some embodiments, the mixing step uses a ball mill or a jar mill, a plowshare mixer or a high-speed mixer to mix the materials evenly, and then put them into a small dry pot or a sagger, shake them evenly, cut them into pieces, and then sinter them for the second time.
[0047] In some embodiments, the second sintering step includes: heating to 380-780° C. (preferably 400-770° C., more preferably 420-760° C.) and keeping warm for 3-16 h (preferably 4-14 h, more preferably 5-12 h) in an oxygen-containing atmosphere (preferably the atmosphere is oxygen with a concentration of ≥95%);
[0048] Preferably, when the second sintering step is carried out in a muffle furnace or a tube furnace mode, the heating rate is controlled to be 1-3°C / min;
[0049] Preferably, when the second sintering step is carried out in an atmosphere roller kiln or a rotary kiln mode, the heating rate is controlled to be 1-20° C. / h.
[0050] Step (3):
[0051] In some embodiments, the ratio of the total molar amount of Ni, Co, and Mn in the positive electrode material after the first coating to the total molar amount of Ti, P, and Li in the second coating agent is 1: (0.0001-0.0060).
[0052] In some embodiments, the second coating agent containing Ti / P / Li includes TiP2O7 or Ti3(PO4)4, and anhydrous LiOH or anhydrous C2H3O2Li;
[0053] Preferably, the mass ratio of the positive electrode material after the first coating to TiP2O7 is 100:(0.05-0.50), preferably 100:(0.07-0.46), more preferably 100:(0.09-0.40); or the mass ratio of the positive electrode material after the first coating to Ti3(PO4)4 is 100:(0.02-0.40), preferably 100:(0.07-0.36), more preferably 100:(0.09-0.30);
[0054] Preferably, the purity of TiP2O7 is ≥99.0%, and its D 50 Particle size 100nm-400nm; or Ti3(PO4)4 purity ≥99.0%, its D 50 Particle size 100nm-400nm.
[0055] Preferably, the mass ratio of the positive electrode material after the first coating to anhydrous LiOH is 100:(0.03-0.80), preferably 100:(0.05-0.70), more preferably 100:(0.08-0.60); or the mass ratio of the positive electrode material after the first coating to anhydrous C2H3O2Li is 100:(0.04-1.60), preferably 100:(0.08-1.40), more preferably 100:(0.1-1.20);
[0056] Preferably, the purity of anhydrous LiOH is ≥99.5%, and its D 50 Particle size 20nm-60nm; or anhydrous C2H3O2Li purity ≥ 99.0%, its D 50 Particle size 20nm-60nm;
[0057] In some embodiments, the mixing step uses a ball mill or a jar mill, a plowshare mixer or a high-speed mixer to mix the materials evenly, and then put them into a small dry pot or a sagger, shake them evenly, cut them into pieces, and then sinter them for the third time.
[0058] In some embodiments, the third sintering step includes: in an oxygen-containing atmosphere (preferably the atmosphere is oxygen with a concentration of ≥95%), heating to 220-480° C. (preferably 240-470° C., more preferably 260-460° C.) and keeping warm for 2-12 h (preferably 3-11 h, more preferably 4-10 h);
[0059] Preferably, when the third sintering step is carried out in a muffle furnace or a tube furnace mode, the heating rate of the step is controlled to be 1-5°C / min, preferably 2-4°C / min, more preferably 3°C / min;
[0060] Preferably, when the third sintering step is carried out in an atmosphere roller kiln or a rotary kiln mode, the heating rate of the step is controlled to be 1-20°C / h, preferably 5-15°C / h, and more preferably 10°C / h.
[0061] The positive electrode material after the second coating is crushed, screened, demagnetized, and can be mixed evenly in a batch mixing tank, and dry gas (dehydration and carbon dioxide removal) or inert gas is introduced for protection; the batch mixing equipment can be a ribbon batch mixer or a high-speed mixer.
[0062] Preferably, the obtained large particles of the cathode material after the second coating are D 50 9.0-14.6μm, small particle size D 50 2.2-4.6μm.
[0063] In a third aspect, the present invention provides an application of the above-mentioned mixed lithium-coated modified ternary positive electrode material in the preparation of a secondary battery positive electrode sheet or a secondary battery.
[0064] Preferably, the secondary battery comprises a lithium-ion battery.
[0065] The present invention also discloses a secondary battery positive electrode sheet or a secondary battery prepared from the mixed lithium coated modified ternary positive electrode material or the mixed lithium coated modified ternary positive electrode material prepared by the method.
[0066] Technical effects:
[0067] The mixed lithium-coated modified ternary positive electrode material of the present invention is based on the traditional nickel-cobalt-manganese material and is composed of WO3, Zr 0.8 O2Y 0.2 , γ-Al2O3 and H3BO3 are co-doped and modified; wherein, the fluxing effect is introduced by the H3BO3 dopant raw material, and the low melting point characteristic of H3BO3 is used to improve the inward diffusion effect of Zr / Y / Al / B / P / Li, jointly inhibiting the mixed arrangement of cations, increasing the interlayer spacing, and improving the ion migration ability; the γ-Al2O3 has a certain structural stability when treated at low temperature, and the structural evolution characteristics of the stable α phase transformation at high temperature are further improved. The structure and thermal stability of the nickel-cobalt-manganese ternary material. The mixed lithium coated modified ternary positive electrode material of the present invention is WO3, Zr 0.8 O2Y 0.2, γ-Al2O3 and H3BO3 are co-doped and modified, and Zr / Y / Al / B / W is formed into anion and cation co-doping through high-temperature sintering solid phase reaction, which effectively increases the particle strength and improves the reversible capacity, reduces the side reaction at the interface between the active material and the electrolyte, reduces the solubility of manganese in the organic electrolyte, and effectively improves the cycle performance of the material under high voltage; it can also widen the ion channel and the interlayer distance, improve the discharge efficiency and rate capability of the material; improve the high-temperature electrochemical properties of the material, reduce the degree of Li / Ni mixing, and ensure the application performance of the battery product.
[0068] The mixed lithium coated modified ternary positive electrode material of the present invention further adopts Li3PO4, TiO2 and γ-Al2O3 as coating agents for a coating modification; wherein, the surface electrolyte corrosion resistance and surface oxidation characteristics of the ternary positive electrode material under high voltage are improved by using γ-Al2O3 and TiO2 coating, and the surface particle morphology of Li3PO4 is repaired under appropriate conditions to reduce the impedance of the battery cell; at the same time, after the surface is coated with Li3PO4, TiO2 and γ-Al2O3, a lithium titanium aluminum phosphate fast ion conductor is generated under high-temperature solid phase synthesis conditions, which can effectively improve the surface conductivity and ion migration ability of the material; the fast ion conductor and PO4 can improve the corrosion resistance of the particle surface against hydrofluoric acid, inhibit the generation and production of microcracks, and improve the high-temperature oxidation resistance, reduce the surface impedance, improve the surface electronic conductivity, improve the first discharge efficiency and cycle performance, and ensure the application performance of the battery product.
[0069] The mixed lithium coated modified ternary positive electrode material of the present invention further adopts anhydrous C2H3O2Li or anhydrous LiOH and TiP2O7 or Ti3(PO4)4 as coating agents for secondary coating modification; wherein, by utilizing the low melting point characteristics of C2H3O2Li and LiOH, the surface particle morphology can be repaired under suitable conditions to improve SEM; at the same time, the surface reaction and diffusion effect of TiP2O7 or Ti3(PO4)4 is improved, and the surface formation of lithium titanium phosphate conductor can be promoted, which can effectively improve the surface conductivity and ion migration ability of the material, effectively inhibit the surface oxygen defect phase, further improve the high temperature oxidation resistance, reduce the surface impedance, improve the surface electronic conductivity, improve the first discharge efficiency and cycle performance, and ensure the application performance of the battery product.
[0070] The ternary positive electrode material modified by mixed lithium coating of the present invention adopts a composite modification method of multi-element co-doping and coating, and effectively improves the Li / Ni mixed arrangement and particle surface energy band effect in the positive electrode material through the synergistic effect of mixed lithium synergistic W / Zr / Y / Al / B / P doping and Li / Ti / Al / P primary coating and Li / Ti / P secondary coating, improves the structural stability and thermal stability, rate / cycle / storage performance of high-voltage and high-nickel ternary positive electrode materials, improves the gram-specific capacity and first efficiency, and has the advantages of more stable layered structure, higher electronic conductivity, more rate, long cycle performance storage, low cost and high specific capacity. The lithium-ion battery prepared by the ternary positive electrode material provided by the present invention has a higher gram-specific capacity, rate, safety and cycle performance.
[0071] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 It is a schematic diagram of the structure of the ternary positive electrode material of the present invention;
[0073] Figure 2 The following is a flow chart of the preparation process of the ternary positive electrode material of the present invention;
[0074] Figure 3 The SEM morphology characteristics of the ternary cathode materials prepared in Examples 1-3;
[0075] Figure 4 This is the EDS element characterization diagram of the ternary cathode material prepared in Example 2;
[0076] Figure 5 This is the XRD characterization diagram of the ternary positive electrode material prepared in Example 2;
[0077] Figure 6 The charge and discharge curves of the ternary positive electrode materials prepared in Examples 1-3;
[0078] Figure 7 The cycle curves of the ternary positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-3 are shown. DETAILED DESCRIPTION
[0079] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0080] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0081] In the following embodiments of the present invention, the selected Li3PO4 is prepared by the following steps to obtain lithium phosphate:
[0082] The specific steps are:
[0083] (1) Weigh 30 g of lithium phosphate raw material with a Ca content of 3000 ppm, a Mg content of 1000 ppm, and a Na content of 4000 ppm.
[0084] (2) tributyl phosphate was added with ammonia water to adjust the pH to 10.0-11.0 to obtain 300 ml of tributyl phosphate saponified solution with a concentration of 30%, and the above lithium phosphate raw material was added. The pH was adjusted to between 8.0 and 9.0 with 5% NaOH aqueous solution, the temperature was 27±2°C, and the reaction was carried out for 60 minutes before solid-liquid separation.
[0085] (3) Add 1 / 3 of the volume of water to the extracted organic phase, adjust the pH to 6-8 with 0.5 mol / L HCl aqueous solution, and perform back extraction to obtain a recyclable extract. At this time, the Ca, Mg, and Na impurities in the extracted lithium phosphate are 700 ppm, 450 ppm, and 964 ppm, respectively, as determined by ICP.
[0086] (4) Take 10g of lithium phosphate extracted in step (3) and 50g of ion exchange resin D403, add 200g of deionized water and mix, stir at 200r / min for 2h, then add 50g of ion exchange resin D113 and 200g of deionized water and mix, stir at 300r / min for 2h, and then separate the resin and lithium phosphate with a sieve. At this time, the Ca, Mg, and Na impurities in the lithium phosphate adsorbed by the resin are 300ppm, 230ppm, and 421ppm respectively according to ICP detection.
[0087] (5) The lithium phosphate treated by resin adsorption in step (4) is then subjected to complexation treatment. 100 g of a mixed complexing agent composed of EDTA, nitrilotriacetic acid and glycine powder in a mass ratio of 6:2:2 is mixed with 10 g of lithium phosphate treated in step (4), and then a dilute hydrochloric acid solution is added to adjust the pH to 6-7, the magnetic stirring speed is 300 r / min, and the mixture is heated in a water bath at 60°C for 150 min. After the complexation treatment, the purity of the lithium phosphate and its impurity content can meet the standard requirements of electronic-grade functional materials and positive electrode materials for battery-grade lithium source raw materials. In the experiment, the total yield of lithium phosphate was 93.4%, the purity of lithium phosphate was 99.61% after ICP detection, and the impurities of Ca, Mg and Na were 40 ppm, 61 ppm and 157 ppm respectively.
[0088] (6) The prepared product is ball-milled to obtain a lithium phosphate raw material with a desired particle size.
[0089] In the following embodiments of the present invention, the γ-Al2O3, Zr 0.8 O2Y 0.2 , TiO2, WO3, H3BO3, TiP2O7, C2H3O2Li, Ti3(PO4)4, etc. Such raw materials of the same required specifications can be purchased on the market, or they can be prepared according to traditional synthesis methods and then ground into the required particle size.
[0090] Example 1
[0091] The preparation method of the lithium-mixed coated modified ternary positive electrode material comprises the following steps:
[0092] (1) Prepare the precursor Ni according to the conventional method 0.55 Co 0.15 Mn 0.30 (OH)2(D 50 3.7±0.5μm), Li2CO3(D 50 4±2μm), Li3PO4(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.55 Co 0.15 Mn 0.3 (OH)2 (2000g), Li2CO3 (773.29g), Li3PO4 (80.11g), WO3 (4.60g), Zr 0.80 O2Y 0.20 (5.0g), γ-Al2O3 (5.61g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure dry air or oxygen air (5:5) atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 980℃ for sintering for 10.8h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0093] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.58g), TiO2(D50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm)(3.03g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 760°C in an air atmosphere and sintered for 8.4h, and then crushed and sieved to remove magnetism after cooling to obtain a positive electrode material coated matrix;
[0094] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.22g), C2H3O2Li(D 50 40.0±10.0nm)(8.59g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.8h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0095] Example 2
[0096] The preparation method of the lithium-mixed coated modified ternary positive electrode material comprises the following steps:
[0097] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li2CO3(D 50 4±2μm), Li3PO4(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2 (2000g), Li2CO3 (759.16g), Li3PO4 (83.86g), WO3 (5.30g), Zr 0.80O2Y 0.20 (5.7g), γ-Al2O3 (6.81g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0098] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.56g), TiO2(D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm) (3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. The three powders were then put into a crucible, heated to 720°C and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a positive electrode material coated matrix;
[0099] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.22g), C2H3O2Li(D 50 40.0±10.0nm)(8.59g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.8h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0100] Example 3
[0101] The preparation method of the lithium-mixed coated modified ternary positive electrode material comprises the following steps:
[0102] (1) Prepare the precursor Ni according to the conventional method 0.88 Co 0.07 Mn 0.05 (OH)2(D 50 4.1±0.5μm), LiOH(D50 4±2μm), Li3PO4(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.88 Co 0.07 Mn 0.05 (OH)2 (2000g), LiOH (846.97g), Li3PO4 (86.64g), WO3 (5.75g), Zr 0.80 O2Y 0.20 (6.28g), γ-Al2O3 (7.57g), H3BO3 (3.46g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.6h, then heat to 470℃ for sintering for 4.2h, and then heat to 840℃ for sintering for 14.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0103] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(4.00g), TiO2(D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm)(3.63g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 680°C in an oxygen atmosphere and sintered for 7.6h, and then crushed after cooling and sieved to remove magnetism, to obtain a positive electrode material coated matrix;
[0104] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.91g), C2H3O2Li(D 5040.0±10.0nm) (9.75g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min, and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.0h in an oxygen-air (5:5) atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0105] Comparative Example 1
[0106] The difference from Example 1 is that lithium phosphate mixed lithium and coordinated coating are not used, and secondary coating is not performed. The preparation method of the positive electrode material includes the following steps:
[0107] (1) Prepare the precursor Ni according to the conventional method 0.55 Co 0.15 Mn 0.30 (OH)2(D 50 3.7±0.5μm), Li2CO3(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.55 Co 0.15 Mn 0.3 (OH)2(2000g), Li2CO3(860.84g), WO3(4.60g), Zr 0.80 O2Y 0.20 (5.0g), γ-Al2O3 (5.61g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure dry air or oxygen air (5:5) atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 980℃ for sintering for 10.8h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0108] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent TiO2 (D 5040.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm)(3.03g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 540°C and sintered for 8.4h in a dry air atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a finished product after positive electrode material coating;
[0109] (3) The coated ternary cathode product is put into a batch mixing tank and mixed for 2 hours. The material is sieved to remove the magnetic substance and packaged to obtain the ternary cathode material product, and the relevant physical and chemical data are tested.
[0110] Comparative Example 2
[0111] The difference from Example 2 is that lithium phosphate mixed lithium and coordinated coating are not used, and secondary coating is not performed. The preparation method of the positive electrode material includes the following steps:
[0112] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li2CO3(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2(2000g), Li2CO3(843.51g), WO3(5.30g), Zr 0.80 O2Y 0.20 (5.7g), γ-Al2O3 (6.81g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0113] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent TiO2 (D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm) (3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 460°C and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a finished product after positive electrode material coating;
[0114] (3) The coated ternary cathode product is put into a batch mixing tank and mixed for 2 hours. The material is sieved to remove the magnetic substance and packaged to obtain the ternary cathode material product, and the relevant physical and chemical data are tested.
[0115] Comparative Example 3
[0116] The difference from Example 3 is that lithium phosphate mixed lithium and coordinated coating are not used, and secondary coating is not performed. The preparation method of the positive electrode material includes the following steps:
[0117] (1) Prepare the precursor Ni according to the conventional method 0.88 Co 0.07 Mn 0.05 (OH)2(D 50 4.1±0.5μm), LiOH(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.88 Co 0.07 Mn 0.05 (OH)2 (2000g), LiOH (941.1g), WO3 (5.75g), Zr 0.80 O2Y 0.20(6.28g), γ-Al2O3 (7.57g), H3BO3 (3.46g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.6h, then heat to 470℃ for sintering for 4.2h, and then heat to 840℃ for sintering for 16.8h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0118] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent TiO2 (D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm)(3.63g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then put into a crucible, heated to 530°C and sintered for 8.6h in an oxygen atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a finished product after positive electrode material coating;
[0119] (3) The coated ternary cathode product is put into a batch mixing tank and mixed for 2 hours. The material is sieved to remove the magnetic substance and packaged to obtain the ternary cathode material product, and the relevant physical and chemical data are tested.
[0120] Comparative Example 4
[0121] The difference from Example 2 is that the primary lithium mixing does not use W / Zr / Y / Al / B compounds for collaborative doping modification. The preparation method of the positive electrode material includes the following steps:
[0122] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li2CO3(D 50 4±2μm), Li3PO4(D 50 4±2μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24(OH)2 (2000g), Li2CO3 (759.16g), Li3PO4 (83.86g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0123] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.56g), TiO2(D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm) (3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. The three powders were then put into a crucible, heated to 720°C and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a positive electrode material coated matrix;
[0124] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.22g), C2H3O2Li(D 50 40.0±10.0nm)(8.59g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.8h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0125] Comparative Example 5
[0126] The difference from Example 2 is that no W / Zr / Y / Al / B-containing compound is used for collaborative doping modification, and no Al / Ti-containing compound is used for collaborative coating modification. The preparation method of the positive electrode material comprises the following steps:
[0127] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24(OH)2(D 50 3.6±0.5μm), Li2CO3(D 50 4±2μm), Li3PO4(D 50 4±2μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2 (2000g), Li2CO3 (759.16g), Li3PO4 (83.86g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0128] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.56g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 720℃ and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a positive electrode material coated matrix;
[0129] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.22g), C2H3O2Li(D 50 40.0±10.0nm)(8.59g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.8h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0130] Comparative Example 6
[0131] The difference from Example 2 is that no W / Zr / Y / Al / B-containing compound is used for collaborative doping modification, and no secondary coating modification is performed. The preparation method of the positive electrode material comprises the following steps:
[0132] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li2CO3(D 50 4±2μm), Li3PO4(D 50 4±2μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2 (2000g), Li2CO3 (759.16g), Li3PO4 (83.86g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0133] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.56g), TiO2(D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm) (3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 720℃ and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a finished product after positive electrode material coating;
[0134] (3) The coated ternary cathode product is put into a batch mixing tank and mixed for 2 hours. The material is sieved to remove the magnetic substance and packaged to obtain the ternary cathode material product, and the relevant physical and chemical data are tested.
[0135] Comparative Example 7
[0136] The difference from Example 2 is that no Al / Ti compound is used for the primary coating. The preparation method of the positive electrode material includes the following steps:
[0137] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 503.6±0.5μm), Li2CO3(D 50 4±2μm), Li3PO4(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2 (2000g), Li2CO3 (759.16g), Li3PO4 (83.86g), WO3 (5.30g), Zr 0.80 O2Y 0.20 (5.7g), γ-Al2O3 (6.81g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0138] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.56g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 720℃ and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a positive electrode material coated matrix;
[0139] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.22g), C2H3O2Li(D 5040.0±10.0nm)(8.59g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.8h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0140] Comparative Example 8
[0141] The difference from Example 2 is that no secondary coating is performed. The preparation method of the positive electrode material comprises the following steps:
[0142] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li2CO3(D 50 4±2μm), Li3PO4(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2 (2000g), Li2CO3 (759.16g), Li3PO4 (83.86g), WO3 (5.30g), Zr 0.80 O2Y 0.20 (5.7g), γ-Al2O3 (6.81g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0143] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50100.0±20.0nm)(3.56g), TiO2(D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm) (3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 720℃ and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a finished product after positive electrode material coating;
[0144] (3) The coated ternary cathode product is put into a batch mixing tank and mixed for 2 hours. The material is sieved to remove the magnetic substance and packaged to obtain the ternary cathode material product, and the relevant physical and chemical data are tested.
[0145] Comparative Example 9
[0146] The difference from Example 2 is that only lithium phosphate is not used for the first coating. The preparation method of the positive electrode material includes the following steps:
[0147] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li2CO3(D 50 4±2μm), Li3PO4(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2 (2000g), Li2CO3 (759.16g), Li3PO4 (83.86g), WO3 (5.30g), Zr 0.80 O2Y 0.20(5.7g), γ-Al2O3 (6.81g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0148] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent TiO2 (D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm) (3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. The three powders were then put into a crucible, heated to 720°C and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a positive electrode material coated matrix;
[0149] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.22g), C2H3O2Li(D 50 40.0±10.0nm)(8.59g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.8h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0150] Comparative Example 10
[0151] The difference from Example 2 is that lithium phosphate is not used for lithium mixing / doping, and other oxides are not used to cooperate with lithium phosphate for primary coating. The preparation method of the positive electrode material includes the following steps:
[0152] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li2CO3(D 504±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2(2000g), Li2CO3(843.51g), WO3(5.30g), Zr 0.80 O2Y 0.20 (5.7g), γ-Al2O3 (6.81g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0153] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.56g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 720℃ and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a positive electrode material coated matrix;
[0154] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.22g), C2H3O2Li(D 50 40.0±10.0nm)(8.59g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.8h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0155] Comparative Example 11
[0156] The only difference from Example 2 is that the first lithium mixing does not use lithium phosphate mixing and doping. The preparation method of the positive electrode material includes the following steps:
[0157] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li2CO3(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2(2000g), Li2CO3(843.51g), WO3(5.30g), Zr 0.80 O2Y 0.20 (5.7g), γ-Al2O3 (6.81g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0158] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.56g), TiO2(D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 5080.0±20.0nm) (3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. The three powders were then put into a crucible, heated to 720°C and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a positive electrode material coated matrix;
[0159] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.22g), C2H3O2Li(D 50 40.0±10.0nm)(8.59g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.8h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0160] Comparative Example 12
[0161] The difference from Example 2 is that lithium phosphate is not mixed with lithium and doped, and secondary coating is not performed. The preparation method of the positive electrode material includes the following steps:
[0162] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li2CO3(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2(2000g), Li2CO3(843.51g), WO3(5.30g), Zr 0.80 O2Y 0.20(5.7g), γ-Al2O3 (6.81g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0163] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.56g), TiO2(D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm) (3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 720℃ and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a finished product after positive electrode material coating;
[0164] (3) The coated ternary cathode product is put into a batch mixing tank and mixed for 2 hours. The material is sieved to remove the magnetic substance and packaged to obtain the ternary cathode material product, and the relevant physical and chemical data are tested.
[0165] Comparative Example 13
[0166] The only difference from Example 2 is that no lithium carbonate or lithium hydroxide is used in the first lithium mixing. The preparation method of the positive electrode material comprises the following steps:
[0167] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li3PO4(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.68Co 0.08 Mn 0.24 (OH)2(2000g), Li3PO4(810.91g), WO3(5.30g), Zr 0.80 O2Y 0.20 (5.7g), γ-Al2O3 (6.81g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0168] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.56g), TiO2(D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm)(3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 720℃ and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a substrate coated with a positive electrode material;
[0169] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.22g), C2H3O2Li(D 50 40.0±10.0nm)(8.59g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.8h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0170] Comparative Example 14
[0171] The only difference from Example 2 is that lithium carbonate or lithium hydroxide is not used in the primary lithium mixing, and lithium phosphate is not used for the primary coating. The preparation method of the positive electrode material includes the following steps:
[0172] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li3PO4(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2(2000g), Li3PO4(810.91g), WO3(5.30g), Zr 0.80 O2Y 0.20 (5.7g), γ-Al2O3 (6.81g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0173] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent TiO2 (D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm) (3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. The three powders were then put into a crucible, heated to 720°C and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a positive electrode material coated matrix;
[0174] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.22g), C2H3O2Li(D 5040.0±10.0nm)(8.59g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.8h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0175] Comparative Example 15
[0176] The difference from Example 2 is that only lithium phosphate is used as the lithium source in the first lithium mixing, lithium carbonate or lithium hydroxide is not mixed, and other dopants are not used for synergistic modification. The preparation method of the positive electrode material includes the following steps:
[0177] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li3PO4(D 50 4±2μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2 (2000g), Li3PO4 (810.91g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0178] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.56g), TiO2(D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm) (3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. The three powders were then put into a crucible, heated to 720°C and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a positive electrode material coated matrix;
[0179] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent TiP2O7 (D 50 200.0±20.0nm)(4.22g), C2H3O2Li(D 50 40.0±10.0nm)(8.59g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 320°C for 6.8h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a batch mixing tank and mixed for 2h. The finished product of the ternary positive electrode material was sieved for demagnetization and packaged, and the relevant physical and chemical data were tested.
[0180] Comparative Example 16
[0181] The difference from Example 2 is that the primary lithium mixing uses only lithium phosphate, a dopant and a primary coating agent, and does not use lithium carbonate or lithium hydroxide for mixing, and does not perform secondary coating. The preparation method of the positive electrode material includes the following steps:
[0182] (1) Prepare the precursor Ni according to the conventional method 0.68 Co 0.08 Mn 0.24 (OH)2(D 50 3.6±0.5μm), Li3PO4(D 50 4±2μm) and dopant WO3(D 50 2.0±1.0μm), Zr 0.80 O2Y 0.20 (D 50 2.0±1.0μm),γ-Al2O3(D 50 1.5±1.0μm), H3BO3(D 50 2.0±0.5μm) raw materials, weigh Ni 0.68 Co 0.08 Mn 0.24 (OH)2(2000g), Li3PO4(810.91g), WO3(5.30g), Zr 0.80 O2Y 0.20(5.7g), γ-Al2O3 (6.81g), H3BO3 (4.62g); transfer the materials into a high-speed mixer, use a three-stage mode of 200rmp / 2min, 800rpm / 20min, 100rmp / 3min to mix the three powders evenly, put them into a crucible and transfer them into an atmosphere muffle furnace, in a slightly positive pressure oxygen atmosphere, heat to 320℃ at a rate of 2℃ / min for sintering for 3.2h, then heat to 770℃ for sintering for 3.6h, and then heat to 946℃ for sintering for 12.2h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix is obtained;
[0183] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent Li3PO4 (D 50 100.0±20.0nm)(3.56g), TiO2(D 50 40.0±20.0nm)(2.14g),γ-Al2O3(D 50 80.0±20.0nm) (3.33g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 720℃ and sintered for 8.4h in an oxygen or oxygen-air (5:5) atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a finished product after positive electrode material coating;
[0184] (3) The obtained coated ternary cathode product is put into a batch mixing tank and mixed for 2 hours. The material is sieved to remove the magnetic substance and packaged to obtain the ternary cathode material product, and the relevant physical and chemical data are tested.
[0185] Experimental example
[0186] 1. Physical and chemical indicators
[0187] The positive electrode materials prepared in the above Examples 1-3 and Comparative Examples 1-16 were respectively tested for element and impurity content, and the physical and chemical indicators of the samples were analyzed using relevant equipment such as a scanning electron microscope, a laser particle size instrument, and a Swiss Metrohm automatic titration instrument familiar to technicians. The test results are shown in Table 1 below.
[0188] The SEM images of the ternary cathode materials prepared in Examples 1-3 are shown in Figure 3 Further, EDS test was performed on Example 2 during SEM characterization, and the characterization results are shown in Figure 4 The XRD characterization diagram of the ternary cathode material prepared in Example 2 is as follows: Figure 5 .
[0189] Table 1 Physical and chemical index results of ternary positive electrode materials of Examples 1-3 and Comparative Examples 1-16
[0190]
[0191] It can be seen that the test data of the basic physical and chemical indicators of the Ni5515, Ni6808, and Ni8807 ternary positive electrode single crystal materials in Examples 1-3 show that the performance indicators related to tapping and residual alkali have been improved and enhanced, and have better performance advantages.
[0192] 2. Cycle performance test
[0193] The positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-16 were prepared into lithium-ion batteries (active material: PVDF:CNT:SP=97.2:1.1:0.8:0.9, solid content 73.5%) using methods well known to those skilled in the art, and the obtained positive electrode materials were assembled into button batteries.
[0194] Using the Blue Electric test system, the first charge and discharge specific capacity (see Figure 6 The results are shown in Table 2 below:
[0195] Table 2 Rate discharge / cycle performance test results
[0196]
[0197] The cycle retention rate of the above-mentioned charge-discharge condition of 100 weeks was tested under 1C charge-discharge conditions. The test results are shown in Figure 7 As shown, Figure 7 (a) is the result of Example 1 and Comparative Example 1, (b) is the result of Example 2 and Comparative Example 2, and (c) is the result of Example 3 and Comparative Example 3.
[0198] It can be seen that the gram-to-gram capacity of the ternary positive electrode material prepared by the present invention has been improved year-on-year, and the rate discharge performance and cycle performance have been improved.
[0199] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A lithium-mixed coated modified ternary positive electrode material, characterized in that: It includes a core, and a first coating layer and a second coating layer on the surface of the core; The general formula of the core is Li(Ni x Co y Mn 1-x-y ) z (Y a W b Al c Zr d B e ) f PO4, where 0.5≤x<1.0, 0<y≤0.40, 0.97≤z<1.0, 0<a≤0.0025, 0<b≤0.009, 0<c≤0.008, 0<d≤0.0085, 0<e≤0.002, a+b+c+d+e=f, z:f=(0.97-1.0):(0.0004-0.03), z+f=1; The general formula of the first coating layer is Li3Al x1 Ti y1 (PO4)3, where x1 = 0.2-0.8, y1 = 1.2-1.8; The general formula of the second coating layer is LiTi x2 (PO4)3, where x2 = 0.8-3.
0.
2. A method for preparing the mixed lithium-coated modified ternary positive electrode material according to claim 1, characterized in that: The steps include: (1) Ni x Co y Mn 1-x-y (OH)2 (0.5≤x<1.0, 0<y≤0.40), the first lithium source, the second lithium source and the dopant containing Y / W / Al / Zr / B elements are mixed and sintered for the first time, and then crushed, sieved and demagnetized to obtain the positive electrode material core Li (Ni x Co y Mn 1-x-y ) z (Y a W b Al c Zr d B e ) f PO4; (2) mixing the positive electrode material core with the first coating agent containing Ti / Al / P / Li elements and performing a second sintering, and then crushing, screening, and demagnetizing to obtain the positive electrode material after the first coating; (3) The positive electrode material after the first coating is mixed with the second coating agent containing Ti / P / Li and then sintered for the third time, and then crushed, screened, demagnetized, and batch mixed to obtain a finished positive electrode material after the second coating.
3. The preparation method according to claim 2, characterized in that: In step (1), the first lithium source is one or more selected from LiOH, LiOH·H2O, Li2CO3, LiNO3 or C2H3O2Li, preferably LiOH or Li2CO3; the second lithium source is Li3PO4; The mass ratio of the first lithium source to the second lithium source is 0.5-1.0:0.003-0.
5.
4. The preparation method according to claim 2, characterized in that: In step (1), the ratio of the total molar amount of Ni, Co, and Mn in the ternary positive electrode material precursor, the molar amount of Li in the total lithium source, and the total molar amount of Y, W, Al, Zr, and B in the dopant is 1: (0.94-1.18): (0.0004-0.0300), preferably 1: (0.96-1.15): (0.0008-0.025), and more preferably 1: (0.98-1.10): (0.001-0.020).
5. The preparation method according to claim 2, characterized in that: In step (1), the dopant containing Y / W / Al / Zr / B elements is γ-Al2O3, Zr 0.8 O2Y 0.2 , a mixture of WO3 and H3BO3; Ternary cathode material precursor Ni x Co y Mn 1-x-y The mass ratio of (OH)2 to γ-Al2O3 is 100:(0.03-0.9), preferably 100:(0.08-0.8), more preferably 100:(0.1-0.6); Ternary cathode material precursor Ni x Co y Mn 1-x-y (OH)2 and Zr 0.8 O2Y 0.2 The mass ratio is 100:(0.04-0.60), preferably 100:(0.06-0.52), more preferably 100:(0.1-0.42); Ternary cathode material precursor Ni x Co y Mn 1-x-y The mass ratio of (OH)2 to WO3 is 100:(0.02-0.60), preferably 100:(0.05-0.50), more preferably 100:(0.1-0.40); Ternary cathode material precursor Ni x Co y Mn 1-x-y The mass ratio of (OH)2 to H3BO3 is 100:(0.02-0.7), preferably 100:(0.04-0.6), and more preferably 100:(0.08-0.5).
6. The preparation method according to claim 2, characterized in that: In step (1), the first sintering includes: heating to 650-1100° C. and keeping the temperature for 8-24 hours in an oxygen-containing atmosphere.
7. The preparation method according to claim 2, characterized in that: In step (2), the ratio of the total molar amount of Ni, Co, and Mn in the positive electrode material core to the total molar amount of Ti, Al, P, and Li in the first coating agent is 1: (0.0001-0.0060); Preferably, the first coating agent containing Ti / Al / P / Li elements is a mixture of Li3PO4, TiO2 and γ-Al2O3; The mass ratio of the positive electrode material core to Li3PO4 is 100:(0.02-0.70), preferably 100:(0.05-0.60), and more preferably 100:(0.1-0.50); The mass ratio of the positive electrode material core to TiO2 is 100:(0.01-0.30), preferably 100:(0.04-0.24), and more preferably 100:(0.06-0.20); The mass ratio of the positive electrode material core to γ-Al2O3 is 100:(0.06-0.50), preferably 100:(0.08-0.44), and more preferably 100:(0.1-0.36).
8. The preparation method according to claim 2, characterized in that: In step (2), the second sintering includes: heating to 380-780° C. and keeping the temperature for 3-16 hours in an oxygen-containing atmosphere.
9. The preparation method according to claim 2, characterized in that: In step (3), the ratio of the total molar amount of Ni, Co, and Mn in the positive electrode material after the first coating to the total molar amount of Ti, P, and Li in the second coating agent is 1: (0.0001-0.0060); The second coating agent containing Ti / P / Li includes TiP2O7 or Ti3(PO4)4, and anhydrous LiOH or anhydrous C2H3O2Li; Preferably, the mass ratio of the positive electrode material after the first coating to TiP2O7 is 100:(0.05-0.50), preferably 100:(0.07-0.46), more preferably 100:(0.09-0.40); or the mass ratio of the positive electrode material after the first coating to Ti3(PO4)4 is 100:(0.02-0.40), preferably 100:(0.07-0.36), more preferably 100:(0.09-0.30); The mass ratio of the positive electrode material after the first coating to anhydrous LiOH is 100:(0.03-0.80), preferably 100:(0.05-0.70), more preferably 100:(0.08-0.60); or the mass ratio of the positive electrode material after the first coating to anhydrous C2H3O2Li is 100:(0.04-1.60), preferably 100:(0.08-1.40), more preferably 100:(0.1-1.20); Preferably, in step (3), the third sintering comprises: heating to 220-480° C. and maintaining the temperature for 2-12 hours in an oxygen-containing atmosphere.
10. Use of the hybrid lithium-coated modified ternary positive electrode material according to claim 1 or the hybrid lithium-coated modified ternary positive electrode material prepared by the preparation method according to any one of claims 2 to 9 in preparing a secondary battery positive electrode sheet or a secondary battery.
Citation Information
Cited By
Oxide solid electrolyte material and preparation method and application thereof
CN119852507A
An oxide solid electrolyte material, a method for preparing the same, and an application thereof
CN119852507B
Multi-element co-doped and multi-stage step-coated single-crystal lithium cobalt oxide cathode material and preparation method thereof
CN122762662A
